Organizational Economics: An Impending Revolution in Organization Theory? - Hesterly, William S.; Liebeskind, Julia Porter; Zenger, Todd (Academy of Management Review, 1990)
Organizational economics (OE) is purported to offer a potential revolution in organization theory. This paper assesses the value of organizational economics for organization theorists. The conclusions are that OE is useful in extending theory building and empirical research in organization theory, but for OE to realize its full potential, it must draw upon organization theory to refine theory building and expand its scope.